2012
DOI: 10.2527/jas.2011-4547
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen excretion at different stages of growth and its association with production traits in growing pigs1

Abstract: The objectives of this study were to determine nitrogen loss at different stages of growth and during the entire growing period and to investigate the associations between nitrogen excretion and production traits in growing pigs. Data from 315 pigs of an F(2) population which originated from crossing Pietrain sires with a commercial dam line were used. Nitrogen retention was derived from protein retention as measured using the deuterium dilution technique during different stages of growth (60 to 90 kg, 90 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 17 publications
4
32
0
3
Order By: Relevance
“…Shirali et al. () also showed that N excretion has a large positive correlation with FCR and a moderate negative correlation with ADG. Similarly, the results of the current study show that excretion of nutrients decreases with an improvement in FCR and increase in ADG.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Shirali et al. () also showed that N excretion has a large positive correlation with FCR and a moderate negative correlation with ADG. Similarly, the results of the current study show that excretion of nutrients decreases with an improvement in FCR and increase in ADG.…”
Section: Discussionmentioning
confidence: 91%
“…As Wall, Simm, and Moran () illustrated, environmental impacts of livestock production can be reduced in broad breeding goals by indirect selection on correlated traits of animal productivity and efficiency. An improvement in feed efficiency, for example, reduces nitrogen excretion of fattening pigs (Shirali et al., ). An improvement of feed efficiency reduces the production of effluent per unit of product and reduces emission associated with feed production.…”
Section: Introductionmentioning
confidence: 99%
“…This region was not associated with any other trait analysed in this study suggesting that this is a unique QTL for nitrogen efficiency. However, Gilbert et al [7] reported a QTL for ADFI around this region (83 cM), which would suggests that the increase in ADNE may be due to an increase in feed intake as these traits are highly correlated [11]. …”
Section: Discussionmentioning
confidence: 99%
“…NEWG was the ratio between ADNE and ADG, and the TNE was calculated as ADNE multiplied by days of growth. More detailed information about the nitrogen excretion traits outlined above is presented in a previous study [11]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation